Initial interaction of herpes simplex virus with cells is binding to heparan sulfate. - WuDunn, D (1989)
We have shown that cell surface heparan sulfate serves as the initial receptor for both serotypes of herpes simplex virus (HSV). We found that virions could bind to heparin, a related glycosaminoglycan, and that heparin blocked virus adsorption. Agents known to bind to cell surface heparan sulfate blocked viral adsorption and infection. Enzymatic digestion of cell surface heparan sulfate but not of dermatan sulfate or chondroitin sulfate concomitantly reduced the binding of virus to the cells and rendered the cells resistant to infection. Although cell surface heparan sulfate was required for infection by HSV types 1 and 2, the two serotypes may bind to heparan sulfate with different affinities or may recognize different structural features of heparan sulfate. Consistent with their broad host ranges, the two HSV serotypes use as primary receptors ubiquitous cell surface components known to participate in interactions with the extracellular matrix and with other cell surfaces.